Hazardous metropolis : flooding and urban ecology in Los Angeles - Orsi, Jared, 1970- (University of California Press, 2004)
Despite having 114 debris dams, 5 flood control basins & nearly 500 miles of paved river channels, Los Angeles still struggles to cope with the threat of flash flooding. Orsi advances a new paradigm - the urban ecosystem - for understanding the city's complex & unpredictable waterways.